Cost-effectiveness analysis of the implementation of a National Immunization Program for rotavirus vaccination in a country with a low rotavirus gastroenteritis-related mortality: A South Korean study. Issue 35 (14th August 2019) - Lee, Hankil; Park, Seon Young; Clark, Andrew; Debellut, Frédéric; Pecenka, Clint; Kim, Dong Soo; Kim, Hwang Min; Kim, Ji Hong; Cho, Hyeonseok; Kim, Ah-Young; Lee, Minjun; Jung, Sun-Young; et al.
Abstract: Rotavirus is a leading cause of severe gastroenteritis among children younger than 5 years in South Korea. Two rotavirus vaccines (RVs), pentavalent human-bovine reassortant vaccine (Rotateq®; RV5) and attenuated human strain originated monovalent vaccine (Rotarix®; RV1), have been available for voluntary vaccination using out-of-pocket payment since 2007 and 2008, respectively. Yet, RVs are not included in the National Immunization Program (NIP), partly because of the low associated mortality rate. We assessed the cost-effectiveness of RVs to assist the evidence-based decision-making process for NIP implementation in South Korea. Using a transparent age-structured static cohort model, we simulated the experience of ten annual birth cohorts of South Korean children from 2018 to 2027. Model inputs included rotavirus gastroenteritis (RVGE) incidence and mortality rates, RVGE treatment costs, vaccine coverage and timeliness, and vaccine effectiveness and price. The incremental costs of including RVs in the NIP compared to no vaccination were 59, 662, 738 USD and 152, 444, 379 USD for RV1 and RV5, respectively. The introduction of RV1 and RV5 can prevent 4799 disability-adjusted life years (DALYs) and 5068 DALYs. From the societal perspective, the incremental cost-effectiveness ratios (ICERs) for adopting RV into the NIP versus no vaccination were 12, 432 USD per DALY averted for RV1 and 30, 081 USD per DALY averted for RV 5. The weighted average for the ICERs of the two vaccines computed using the market share of each vaccine in the current voluntary use as a weight, was 21, 698 USD per DALY averted. The estimated ICER was below 1 × gross domestic product per capita (30, 000 USD), which has been a commonly used willingness-to-pay threshold for health care technology assessment in South Korea, suggesting that introducing RVs into the NIP would be cost-effective.